1990
DOI: 10.1007/bf00176666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic substrates on biological sulphide oxidation

Abstract: Neither acetate nor higher fatty acids and glucose have a significant effect on the biotechnological process for sulphide removal at 20 degrees C, in which sulphide is oxidized to sulphur using oxygen. The oxidation of acetate and propionate with oxygen is mainly dependent on the sulphide and oxygen concentrations in the reactor. The occurrence of Thiothrix filaments in sulphide-removing waste-water treatment systems has been investigated using a fixer-film upflow reactor. The influent of this reactor consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…This change has been observed and attributed to H 2 S diffusion (Bowker, 1999). Buisman et al (1990) suggested that the presence of sulfide might result in a shift to filamentous organisms in AS such as Beggiatoa and Thiothrix. However the primary group of bacteria that metabolize sulfur compounds also include non-filamentous microorganisms such as those from the genera Thiobacillus, Thiomicrospira and Thiosphaera.…”
Section: Effects Of As Odor Diffusion On the Process Biologymentioning
confidence: 98%
“…This change has been observed and attributed to H 2 S diffusion (Bowker, 1999). Buisman et al (1990) suggested that the presence of sulfide might result in a shift to filamentous organisms in AS such as Beggiatoa and Thiothrix. However the primary group of bacteria that metabolize sulfur compounds also include non-filamentous microorganisms such as those from the genera Thiobacillus, Thiomicrospira and Thiosphaera.…”
Section: Effects Of As Odor Diffusion On the Process Biologymentioning
confidence: 98%
“…Completely mixed, continuously fed biological reactors were used,each containing reticulated polyurethane foam particles in a hybrid fixed-film activated sludge configuration, now recognized as a moving bed bioreactor (MBBR). Buisman et al (1990b) showed that the addition of organics to the influent resulted in a negligible effect on sulfide removal, but that excessive organic material may have promoted the growth of Thiothrix spp. Thiothrix spp.…”
Section: Carbon Disulfidementioning
confidence: 98%
“…In biofilters, it has been shown that the presence of hydrogen sulfide has no inhibitory effects on the biodegradation of carbon disulfide, or vice versa (Yang et al, 1994c). Buisman et al (1990b) studied the effects of organic substrates, including acetate and proprionate, on biological sulfide oxidation. During the study, filamentous bacteria consistent with Thiothrix spp.…”
Section: Carbon Disulfidementioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, the major innovative development of the Ae micro WT-system lies in its capacity to convert reduced Scompounds into elementary sulfur [31][32][33][34][35][36][37]; the system enables a high rate and low-cost bio-conversion of volatile S-compounds like H 2 S and methanethiol from polluted gases, e.g., from Liquefied petroleum gas (LPG) [38][39][40][41] and from natural gas and/or biogas. The system is effective up to removal capacities of 50 tons H 2 S/day; for higher loads tentatively the well-proven amine/Claus process still looks more attractive [40].…”
Section: Nbm-route Based Waste (Water) Treatment Tackles In Epsusmentioning
confidence: 99%